Analysis of Locutionary Speech Acts on the Twitter Account @Cursedkidd - Astuti, Maguna Eli; Purwanto, Andri; Fidinilah, Mildan Arsdan; Suwandi, Sahri; Annisa, Fitriah; Nazila, Hidayatun (Linguistics and ELT Journal, 2025)
This study aims to analyze locutionary speech acts used in the Twitter account @Cursedkidd using a pragmatic approach and qualitative methods. Locutionary speech acts are understood as literal utterances that function to convey information directly in communication interactions. This study explores the forms of locutionary speech acts such as directives, declaratives, interrogatives, imperatives, and expressives, and how these forms are used to build public discourse through Twitter social media. Data were collected through observation of tweets and replies from the @Cursedkidd account, then analyzed using listening techniques and discourse analysis methods. The results showed that the dominant locutionary forms were directives (40%), followed by declaratives (32%), interrogatives and imperatives each (10%), and expressives (8%). These findings indicate that Twitter as a social media creates an interactive and dynamic communication space, where concise language styles, symbols, and popular cultural elements such as slang are used strategically to influence, express emotions, and build social relationships. This study emphasizes the importance of understanding social and cultural contexts in interpreting literal meanings and interactions in digital media.